THE HISTORY OF THE INTERSTATE RELATIONS BETWEEN THE REPUBLIC OF KAZAKHSTAN AND INDIA AT THE END OF XX – THE BEGINNING OF THE XXI CENTURY (International relations and international law Journal, 2016)
This article focuses on the evolution of bilateral relations of the Republic of Kazakhstan and India. The article deals with the process of political, diplomatic and economic relations between the two countries in the end of XX – beginning of XXI centuries.Revealed some features of the bilateral cooperation between Kazakhstan and India. Indicates a positive value for the development of bilateral relations of the two economies.
Keywords: Republic of Kazakhstan; India; foreign policy